AUTONOMOUS MOBILE-ASSISTED LANGUAGE LEARNING FOR YOUNG LEARNERS USING DUOLINGO - Nurul Annisa Saraswati; Syafi’ul Anam; Oikurema Purwati (University of Muhammadiyah Malang, 2021)
Learning English through Mobile-Assisted Language Learning (MALL) platforms has become a demand in English for Foreign (EFL) and English for Second Language (ESL) learners globally, and one of the platforms is Duolingo. This case study was conducted in order to find out the impact of Duolingo, which is assumed to be useful in enhancing self-regulated learning for young learners and the parents’ attitude in supporting the learning. This study used a qualitative method in data analysis, and the data were collected through observation and semi-structured interviews of the participant and the parents. The finding of this study revealed that the use of Duolingo could enhance the learner motivation and attitudes in learning English autonomously as well as actively practicing the language in a real situation. The participant showed active engagement in learning English autonomously with Duolingo, and the parents also found the platform to be useful in supporting the participant’s learning process. Hence, in this study, learning English through the Duolingo application can support autonomous EFL learning without the barrier of space and time. However, as this research was a small-scale case study, and further research is recommended with a larger scale of participants and other MALL applications.